Physiotherapy Counseling for Trigger Finger Cases in the Posyandu Community in Rampal Celaket, Malang City - Intan Aulia Pebra; Moh. Ali Sahib; Kurnia Putri Utami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Trigger finger, also known as stenosing tenosynovitis, is a hand disorder generally caused by inflammation or narrowing of the flexor tendons that control finger movement. This disorder can result in difficulty in fully clenching or opening the fingers, as well as significant pain or discomfort. Education about trigger finger cases is an important approach in the management and prevention of this disease. Trigger finger case education involves an in-depth understanding of the causes, symptoms, diagnosis, and available treatment options. Through education, individuals can understand the risk factors for jobs that involve excessive use of their hands or certain diseases that can increase their risk of developing trigger finger. This education can help people increase their knowledge about treatment to reduce the risk of this disease, such as stretching their hands regularly and using ergonomic techniques. The achievement of the final evaluation of community knowledge after counseling is from 8,1% to 100%. Trigger finger prevention process from the beginning was unknown to the target community. Education through the counseling process still needs to be carried out.